Executive Functions in Alzheimer Disease: A Systematic Review - Guarino, Angela; Favieri, Francesca; Boncompagni, Ilaria; Agostini, Francesca; Cantone, Micaela; Casagrande, Maria (Frontiers in Aging Neuroscience, 2019)
Alzheimer disease is a severe irreversible syndrome, characterised by a slow and progressive cognitive decline that interferes with the standard instrumental and essential functions of daily life. Promptly identifying the impairment of particular cognitive functions could be a fundamental condition to limit, through preventive or therapeutic interventions, the functional damages found in this degenerative dementia. This study aims to analyse, through a systematic review of the studies, the sensitivity of four experimental paradigms (Wisconsin Card Sorting Test, Stroop Task, Go/No-Go Task and Flanker Task), considered as golden standard instruments for executive functions assessment in elderly subjects affected by Alzheimer dementia. This review was carried out according to the PRISMA-Statement. Forty-five studies comparing the executive performance of patients with Alzheimer dementia (diagnosed according to different classification criteria for dementia) and healthy elderly people, both over the age of sixty, were selected. For the research, PubMed, PsycINFO, PsycArticles databases were used. The study highlighted the importance of using standard protocols to evaluate executive dysfunction in Alzheimer's disease. The Stroop task allows discriminating better between healthy and pathological ageing.